Analysis of the psychophysiological state of Ukrainian basketball players - Andriy Kyyko; Yuliya Volkova; Andrii Poltavets; Vladyslav Yudin; Dmytro Kmetiuk (Universidad de Murcia, 2022)
Article accepted. The article will be published here soon. Pending final quality checks.